2019
DOI: 10.1080/09638288.2019.1610084
|View full text |Cite
|
Sign up to set email alerts
|

Stumbling, struggling, and shame due to spasticity: a qualitative study of adult persons with hereditary spastic paraplegia

Abstract: Purpose: Little is known concerning the impact of chronic spasticity on physical activities, social participation, and well-being, and whether patients' needs are addressed by current treatments. This study aims to investigate these lacunas in persons with a pure form of hereditary spastic paraplegia (HSP), in whom spasticity is a prominent symptom. Methods: Fourteen patients with a pure form of HSP were interviewed. These interviews were recorded, verbally transcribed, and thematically analyzed. Results: Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
4
17
1
1
Order By: Relevance
“…Our results further showed that pain, fatigue, and autonomic problems are major (non-motor) symptoms in patients with pure HSP. Only few previous studies have mentioned pain as an important problem in this population [15,16,18,37], even though pain in the legs and/or back was reported by 72% of our participants. This number was similar to the reported frequency in previous studies [15,18].…”
Section: Muscular and Non-motor Symptomscontrasting
confidence: 55%
See 4 more Smart Citations
“…Our results further showed that pain, fatigue, and autonomic problems are major (non-motor) symptoms in patients with pure HSP. Only few previous studies have mentioned pain as an important problem in this population [15,16,18,37], even though pain in the legs and/or back was reported by 72% of our participants. This number was similar to the reported frequency in previous studies [15,18].…”
Section: Muscular and Non-motor Symptomscontrasting
confidence: 55%
“…The structure and content of the web-based survey were designed by a team of expert physicians, researchers, physical therapists, and persons with HSP. Part of the questionnaire was based on a previous international survey of patients living with spasticity [9], while other questions were based on a qualitative study in patients with pure HSP who were interviewed about the daily life consequences of spastic paraparesis and their related healthcare needs (note: data on healthcare needs are reported elsewhere) [16]. The structure and formulation of the questions and predefined answering options were improved during an iterative process, until all authors agreed on the final questionnaire.…”
Section: Web-based Questionnairementioning
confidence: 99%
See 3 more Smart Citations